Analysis of Students Perception about Teachers’ Personality in the Academic Achievement - Sadaf Umer Chhapra; Saba Naz; Mehmood Usmani; Adil Mohiuddin (TARBIYA: Journal of Education in Muslim Society, 2018)
AbstractThis study is aimed at exploring the relationship of teacher’s personality as perceived by the students with students’ academic achievement. The major objective of the study is to measure the perceptions of students about five dimensions of their teachers’ personality (i.e. Openness, Extraversion, Agreeableness, Conscientiousness, and Neuroticism) and to identify the relationship between these five dimensions of teacher’s personality and students’ academic achievement at the university level. Data is collected from male and female students of five universities of Karachi with the help of questionnaire design on a Likert scale. As the population frame is not available to the random sampling technique (non-probability method) is used to collect data from 385 respondents. Statistical techniques that are applied for analysis of collected data are descriptive analysis, regression and ANOVA analysis. Findings of the study show that there is a significant relationship between teachers’ personality and student’s academic performance at the university level. Furthermore, all personality traits except Neuroticism creates a positive impact on student’s academic output. This study will help teacher and management to better understand the importance of personality traits and their impact on class management and ultimately on student’s academic performance. AbstrakTulisan  ini bertujuan untuk mengeksplorasi hubungan kepribadian guru yang dirasakan oleh siswa dengan prestasi akademik siswa. Tujuan utama penelitian adalah untuk mengukur persepsi siswa tentang lima dimensi kepribadian guru mereka ( yaitu Openness, Extraversion, Agreeableness, Conscientiousness, dan  Neuroticism) dan untuk mengidentifikasi hubungan antara lima dimensi kepribadian guru dan prestasi akademik siswa. di tingkat universitas. Data dikumpulkan dari siswa pria dan wanita dari lima universitas di Karachi dengan bantuan desain kuesioner pada skala likert. Karena kerangka populasi tidak tersedia untuk teknik sampling acak (metode non-probabilitas) digunakan untuk mengumpulkan data dari 385 responden. Teknik statistik yang diterapkan untuk analisis data yang dikumpulkan adalah analisis deskriptif, regresi dan analisis ANOVA. Temuan penelitian menunjukkan bahwa ada hubungan yang signifikan antara kepribadian guru dan kinerja akademik siswa di tingkat universitas. Selain itu, semua ciri kepribadian kecuali Neuroticism menciptakan dampak positif pada output akademik siswa. Penelitian ini membantu guru dan manajemen untuk lebih memahami pentingnya sifat kepribadian dan dampaknya terhadap manajemen kelas dan akhirnya kinerja akademik siswa